Pregnancy in uterus didelphys delivered by caesarean delivery: case report - Rao, Sneha S.; GS, Anitha; P., Chandralekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterus didelphys represents a uterine malformation where the uterus is present as paired organ. There is presence of double uterine bodies with two separate cervices and often a double or septate vagina. Women with congenital malformations of uterus usually have higher incidence of complications during pregnancy and delivery. We report the case in our institute of a pregnancy in the left sided body of a didelphys uterus delivered by caesarean section.